2019
DOI: 10.1021/acsami.9b10967
|View full text |Cite
|
Sign up to set email alerts
|

Control of Nucleation Density in Conjugated Polymers via Seed Nucleation

Abstract: The development of processing methods to precisely control the solution state properties of semiconducting polymers in situ have remained elusive. Herein, a facile solution seed nucleation processing method is presented in which nucleated poly­(3-hexylthiophene) (P3HT) solutions are blended with well-solvated, non-nucleated counterparts as a means to promote the formation of interconnected polymer networks. Nucleation and growth of these networks was induced by preprocessing the solution with UV irradiation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 57 publications
(114 reference statements)
0
22
0
Order By: Relevance
“…The crystallization kinetics of polymeric materials relies on many factors, including chain rigidity, molecular weight, and preexisting microstructures. 21,33 Isothermal crystallization studies have been demonstrated as a powerful method for analyzing the crystallization kinetics of polymers. 36,37 However, such studies for conjugated polymers are challenging because their strong tendency to crystallize makes it difficult to reach a truly amorphous state in which controlled annealing can be carried out.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The crystallization kinetics of polymeric materials relies on many factors, including chain rigidity, molecular weight, and preexisting microstructures. 21,33 Isothermal crystallization studies have been demonstrated as a powerful method for analyzing the crystallization kinetics of polymers. 36,37 However, such studies for conjugated polymers are challenging because their strong tendency to crystallize makes it difficult to reach a truly amorphous state in which controlled annealing can be carried out.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Using morphological characterization methods, people have observed the improved crystallization in P3HT films by introducing aggregations in P3HT solutions through ultrasonication and low-dose UV irradiation. 21,25,55,56 Here, we explored the impact of such preformed H-crystallites on the crystallization behaviors in DPP-based polymers using thermal characterizations enabled by FSC.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the chain conformations of emerging D–A copolymers are more complex than those in homotype conjugated polymers because multiple noncovalent interactions (i.e., π–π interactions, hydrogen bonding, and heteroatom interactions arising from π-conjugated backbones or functional groups) are involved. Therefore, it is difficult to propose general models to predict the crystallization process of rigid conjugated polymers. …”
Section: Optimizing Film Microstructure For Balanced Electrical and M...mentioning
confidence: 99%